Case Report: Mevalonic Aciduria Complicated by Acute Myeloid Leukemia After Hematopoietic Stem Cell Transplantation - Kim, Hyery; Lee, Beom Hee; Do, Hyo-Sang; Kim, Gu-Hwan; Kang, Sunghan; Koh, Kyung-Nam; Im, Ho Joon (Frontiers in Immunology, 2021)
Mevalonic aciduria (MA) is the most severe clinical subtype of mevalonate kinase deficiency (MKD) caused by an inherited defect in the mevalonate pathway. The treatment of MKD focuses on the suppression of recurrent hyperinflammatory attacks using anti-inflammatory drugs. Recently, allogeneic hematopoietic stem cell transplantation (HCT) was shown to successfully ameliorate autoinflammatory attacks in patients with MKD. Here, we report a case of an infant who showed severe recurrent systemic inflammation and was diagnosed with MA. Although she responded to steroids, her symptoms relapsed after the dose was tapered, and organ deterioration occurred. Therefore, at the age of 11 months, HCT from a matched, unrelated donor was performed for curative treatment. However, at 50 days after transplantation, acute myeloid leukemia was diagnosed, which was chemo-refractory. A second HCT from her haploidentical father was performed to treat the acute myeloid leukemia, but the patient died of sepsis on day 4 after transplantation. This is the first report of malignancy following HCT for MA. Our findings suggest that normalizing the mevalonate pathway after HCT in patients with MKD impacts patients differently depending on the clinical spectrum and severity of disease.